Experimental College Bulletin - Experimental College (Tufts Archival Research Center, 2024)
Content Warning: This issue of the Ex-College Bulletin contains a racist depiction of an East Asian man with caricatured features. The drawing, found on page 40 of the PDF/numbered page 39, is meant to accompany the section heading "language studies."